ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI LOYALITAS PELANGGAN PRODUK HANDBODYLOTION MEREK VASELINE (Studi Pada Mahasiswa Universitas Stikubank Semarang) - Ayu Wulandari, 11.05.51.0113 (Students Journal of Economic and Management, 2015)
This study takes an object on University Stikubank Semarang. This study aims to examine and analyze the effect of price perception, brand image, promotion, product quality and customer satisfaction on consumer loyalty in using Vaseline Hand and Body Lotion. Respondents of this study is the students University Stikubank Semarang who use the product Vaseline Handbodylotion numbered as many as 100 people. The sampling technique using purposive sampling, then analyzed using linear regression and methods of data collection using the questionnaire. The test results showed that: (1) price perception, brand image, promotion, product quality and significant positive effect on customer satisfaction, (2) price perception, brand image, promotion, product quality and significant positive effect on customer loyalty, (3) price, brand image, promotion, product quality and significant positive effect on customer loyalty through customer satisfaction. Keywords: price perception, brand image, promotion, product quality, customer satisfaction and custome royalty.